2014
DOI: 10.5144/0256-4947.2014.503
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-DR/DQ polymorphisms with schizophrenia in Tunisian patients

Abstract: BACKGROUND AND OBJECTIVESThe hypothesis that human leukocyte antigens (HLAs) confer susceptibility to schizophrenic disorders has been tested by studying linkage and association in family samples. Our goal was to evaluate the role of HLA in the risk of developing schizophrenia in a Tunisian population.DESIGN AND SETTINGSBlood samples for this case-control study were collected from patients of the Department of Psychiatry at the Military Hospital of Tunisia between July 2012 and May 2013.METHODSA total of 140 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Furthermore, the HLA-DRB1 gene has been a focus in investigating the HLA association with schizophrenia [ 17 ]. A strong positive association between HLA-DRB1*03 and HLA DQB1*02 alleles and schizophrenia has widely been reported in the Saudi and Tunisian populations [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the HLA-DRB1 gene has been a focus in investigating the HLA association with schizophrenia [ 17 ]. A strong positive association between HLA-DRB1*03 and HLA DQB1*02 alleles and schizophrenia has widely been reported in the Saudi and Tunisian populations [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our risk ratio values, other alleles presumably susceptible to alleviate the risk of suicidal behavior are HLA-DQB1*08, *01 or *14 (RR of .6-.7), in contrast to HLA-DQB1*12 (RR 1.67). In accordance with these data, a Tunisian study found the DQB1*02 allele to be the most susceptible and DQB1*05 the most protective in schizophrenia patients [32]. On the other hand, an American study on a huge cohort of mainly Caucasian deceased organ donors [33] which associated intentional violent death with 21 HLA-DR and 10 HLA-DQ alleles found both DQB1*02 and DQB1*05 to be significantly associated with increased risks for violent death.…”
Section: Discussionmentioning
confidence: 75%
“…Gender‐specific associations revealed that DRB1*10:01:01 and DQB1*05:01:01 were positively associated while DQB1*03:02:01 was negatively associated in female subjects with schizophrenia. According to earlier studies, DQB1*05 has been reported to be a protective allele in Tunisians (Sayeh et al., 2014) while DQB1*03 as a susceptible allele in Singapore Chinese population (Nimgaonkar, Rudert, Zhang, TsoiWF, & Saha, 1995), though they were not gender specific. In the present study, DQB1*06:01:01 was found to be a susceptible allele among male subjects with schizophrenia, in contrast to a previous report from Singapore Chinese population where the allele has been reported to be a protective allele (Nimgaonkar et al, 1995).…”
Section: Discussionmentioning
confidence: 93%
“…Haplotype analysis revealed a significant protective association for the haplotypes DRB1*04:03:01~DQB1*03:02:01. However, this haplotype was reported as a susceptible haplotype in Tunisian population (Sayeh et al., 2014). The present study has also brought out that A*01:01:01~B*37:01:01~C*06:02:01~DRB1*10:01:01~DQB1*05:01:01 is the predominant haplotype in schizophrenia population when compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation